Apremilast as a target therapy for nail psoriasis: a real-life observational study proving its efficacy in restoring the nail unit. (17th February 2022) - Lanna, C.; Cesaroni, G. M.; Mazzilli, S.; Vollono, L.; Gaziano, R.; Marino, D.; Bianchi, L.; Campione, E.
Abstract: Purpose: Psoriasis, Psoriatic Arthritis and Nail psoriasis are chronic diseases that share a common underlying etiology of immunity dysregulation, enhanced activation of inflammatory pathways and remitting-relapsing course. Although nails represent a small percentage of the body surface involvement of this site can lead to impaired quality of life, severe discomfort and even result in permanent disability. Current therapeutic options for nail psoriasis include a variety of topical and systemic treatments although they are often reported as unsatisfactory from patients either due to their poor effectiveness or disturbing side effects. Recently small molecule drugs such as the PDE4 inhibitors were introduced in clinical practice and specifically apremilast has shown to be an effective new treatment option for psoriasis and psoriatic arthritis. Considering either the specific mechanism of action of apremilast, we performed a real-life observational study of 24 weeks assessing apremilast role in nail psoriasis. Matherials and methods: Patients received apremilast 30mg bid, orally. Safety and efficacy were assessed at weeks 0, 4, 8, 12 and 24 using Dermatologic Life Quality Index (DLQI) and Nail Area Psoriasis Severity Index (NAPSI). At T0 we took a nail sample to investigate the presence of onychomycosis. Culture tests were performed in all the patients to search for fungi. Results: We recruited a total of 15 patients with nail psoriasis. The analysis of variance (one-way ANOVA) showed the following results: DLQI (F.15.7; p -value < .00001) and NAPSI (F.9.4; p -value < .00001). Three patients (20%) presented also onychomycoses at the beginning of the treatment. Conclusions: Apremilast showed fast and sustained improvement of nail psoriasis over time and a complete resolution of life quality impairment due to the disease.